2021
DOI: 10.1002/jso.26364
|View full text |Cite
|
Sign up to set email alerts
|

Use of the superficial circumflex iliac artery perforator flap for reconstruction after sarcoma resection

Abstract: Background Postoperative complications after flap‐coverage in sarcoma treatment can postpone postoperative adjunct treatments. Here, we present our experience with the use of the superficial circumflex iliac artery perforator (SCIP) flap after sarcoma resection. Patients and Methods Patients undergoing immediate reconstruction surgery with a flap after sarcoma resection at a single institution from February 2017 to April 2020 were identified. Patient demographics, tumor characteristics, surgical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…When using perforator-toperforator anastomosis, it is recommended to select a short-pedicled perforator flap (i.e., PAP, ALT, and SCIP flaps) to match the vessels caliber. 25,26 We must acknowledge several limitations of this study. First, this cadaveric study included possible underestimation of the number of perforators because formalin fixed cadavers were used.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When using perforator-toperforator anastomosis, it is recommended to select a short-pedicled perforator flap (i.e., PAP, ALT, and SCIP flaps) to match the vessels caliber. 25,26 We must acknowledge several limitations of this study. First, this cadaveric study included possible underestimation of the number of perforators because formalin fixed cadavers were used.…”
Section: Discussionmentioning
confidence: 97%
“…When using perforator-to-perforator anastomosis, it is recommended to select a short-pedicled perforator flap (i.e., PAP, ALT, and SCIP flaps) to match the vessels caliber. 25 26…”
Section: Discussionmentioning
confidence: 99%
“…The superficial circumflex iliac artery perforator flap can be used to repair limbs, head, neck, other wounds, and sarcoma in the other parts of the trunk after surgery and also to reconstruct the tongue, breast, penis, and other organs. [12][13][14][15] The superficial external oblique aponeurotic branch, the lymph node branch, the deep branch of the sartorius muscle branch, and the iliac branch can be used to cut multi-tissue chimeric skin flaps, segmented skin flaps, and lymphatic skin flaps. [14] Based on the advantages of multifunction, multipurpose, and hidden supply and demand, this flap is superior to the anterolateral thigh flap commonly used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…While smaller defects can be addressed with primary closure, larger ones necessitate more advanced plastic and reconstructive surgery techniques, such as local or free flap transfers. These reconstruction techniques have been explored extensively in the academic literature [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. With the current improvements in microsurgical techniques and instruments, some recent studies have shown that free flap transfers have a similar safety profile to the reconstruction using a local flap [ 2 , 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%